HIV Prevention Trials Network 078: High Prevalence of Hepatitis C Virus Antibodies Among Urban US Men Who Have Sex With Men, Independent of Human Immunodeficiency Virus Status. (21st December 2020) - Irvin, Risha; Gamble, Theresa; Malone, Jowanna; Wang, Zhe; Wilson, Ethan; Hughes, James P; Farley, Jason; Mayer, Kenneth H; Del Rio, Carlos; Batey, D Scott; Cummings, Vanessa; Remien, Robert H; et al.
Abstract: Background: Sexual transmission of hepatitis C virus (HCV) is uncommon, yet documented among men who have sex with men (MSM), primarily among those with human immunodeficiency virus (HIV). Methods: In the HIV Prevention Trials Network 078 study (HPTN 078), which assessed an integrated strategy to achieve HIV viral suppression, 1305 MSM were screened across 4 geographically diverse US cities. At screening, demographic/behavioral/psychosocial questionnaires were completed, along with HIV and HCV testing. Multivariable logistic regression was used to evaluate associations with HCV antibody positivity. Results: Among the 1287 (99%) of the MSM with HCV antibody results, the median age was 41, 69% were black, 85% had a high school education or more, 35% were employed, 70% had HIV, and 21% had undergone substance use counseling. The median lifetime number of male sexual partners was 17 (interquartile range, 6–50), and 246 (19%) were HCV antibody positive. HCV antibody positivity was high in MSM with HIV (20%) and MSM without HIV (17%) ( P = .12) and was higher in those receiving substance use counseling (36%) than in those who had not (15%) ( P ≤ .01). Substance use counseling (odds ratio, 2.51; 95% confidence interval, 1.80–3.51) and unstable housing (2.16; 1.40–3.33) were associated with HCV antibody positivity. Conclusions: Nearly 1 in 5 MSM screened for HPTN 078 have been infected with HCV. The prevalence is high regardless of HIV status and is high even in those who did not undergo substance use counseling. In HIV burden networks, high HCV infection prevalence may occur in MSM without HIV. As implementation of preexposure prophylaxis expands and condom use declines, routine HCV counseling and screening among MSM are important. Abstract : Nearly 1 in 5 men who have sex with men (MSM) screened for the human immunodeficiency virus (HIV) Prevention Trials Network 078 study have been infected with hepatitis C virus (HCV). The prevalence is high regardless of HIV status. In HIV burden networks, high HCV infection prevalence may occur in MSM without HIV.